2020
DOI: 10.1016/j.jmpt.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposures to Seated Postures With Immediate Increases in Back Pain: A Systematic Review of Studies With Objectively Measured Sitting Time

Abstract: Objective: The purpose of this study was to conduct a systematic review of studies to determine whether sitting time measured objectively (by laboratory controlled time trial, direct observation, or wearable sensor) is associated with the immediate increase in low back pain (LBP) (determined by pain scale rating) in people >18 years of age. Methods: Four databases (PubMed, EMBASE, SPORTDiscus, and Cumulative Index to Nursing and Allied Health Literature) were searched from inception to September 1, 2018. Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 63 publications
0
21
0
2
Order By: Relevance
“…For instance, increased occupational physical activity is reported to be associated with reduced general MSP symptoms [ 133 , 134 , 136 ]. Also, a review of experimental studies has reported that device-measured continuous uninterrupted sitting is associated with the increased immediate report of LBP in adults [ 25 ]. The evidence from our review also suggests experiments/interventions that reduce total workplace sitting time or sitting bout duration potentially reduce general MSP/discomfort, especially in the lower back and the neck/shoulder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, increased occupational physical activity is reported to be associated with reduced general MSP symptoms [ 133 , 134 , 136 ]. Also, a review of experimental studies has reported that device-measured continuous uninterrupted sitting is associated with the increased immediate report of LBP in adults [ 25 ]. The evidence from our review also suggests experiments/interventions that reduce total workplace sitting time or sitting bout duration potentially reduce general MSP/discomfort, especially in the lower back and the neck/shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, an inconsistent body of evidence of associations of SB with MSP conditions and related outcomes from high-level evidence-based studies [ 19 , 20 ]. Some previous systematic reviews of studies including higher-level study designs have reported no associations of SB with the prevalence of some MSP conditions [ 19 24 ], whereas others have reported either positive [ 20 , 25 ] or negative [ 26 ] associations with some MSP-related outcomes such as pain intensity. Methodological differences and limitations within the individual studies reviewed in these systematic reviews could impact the quality of evidence and comparability of these reviews as some of the studies were based on self-reported and surrogate estimates of SB which increases the risk of bias [ 19 , 21 , 22 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 70% of physiotherapists considered the upright lordotic sitting posture as the optimal posture (82). Major stakeholders in the healthcare systems around the world commonly agree that prolonged sitting is associated with a higher prevalence of LBP (25,(83)(84)(85)(86)(87)(88). Sustained sitting for more than thirty minutes is considered a common aggravating factor for many people with LBP (81), although there is a lack of evidence in support of this concept (89)(90)(91).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding workplace factors and the occurrence of LBP, prolonged sitting is commonly cited in the literature, but the available evidence has not confirmed a consistent association between occupational sitting and LBP [ 3 , 4 ]. Nevertheless, office workers spend over two-thirds of their workday seated and this prolonged and uninterrupted sedentary behaviour [ 5 ] is a recognised public health concern [ 6 ].…”
Section: Introductionmentioning
confidence: 99%